Cord-Blood Natural Killer Cell-Based Immunotherapy for Cancer - Zhao, Xiaoyan; Cai, Li; Hu, Yu; Wang, Huafang (Frontiers in Immunology, 2020)
Natural killer (NK) cells are a predominant part of innate immune cells and play a crucial role in anti-cancer immunity. NK cells can kill target cells nonspecifically, and their recognition of target cells is not restricted by the major histocompatibility complex. NK cells also fight against tumor cells independently of antibodies and prior activation. Of note, umbilical cord blood (UCB) is a rich source of NK cells. Immunotherapies based on UCB-derived NK cells are becoming increasingly researched, and the investigations are producing encouraging results. In recent years, non-modified and modified UCB-derived NK cells have been successfully developed to fight against tumor cells. Herein, UCB-derived NK cell-based immunotherapy is a potential strategy for the treatment of cancer in the future. In this review, we focus on discussing the biological characteristics of UCB-derived NK cells and their application prospects in anti-tumor immunotherapy, including the latest preclinical and clinical researches.